Structural biology of lipoxygenases: current knowledge and further development - I. V. Ivanov; N. V. Groza; G. I. Myagkova; H. Kühn (Тонкие химические технологии, 2014)
Lipoxygenases (LOX) form a heterogeneous family of lipid peroxidizing enzymes, which have been implicated in the synthesis of inflammatory mediators. The involvement of LOX isoenzymes in regulation of physiological homeostasis and pathogenesis of various diseases with major health and political relevance made them potential targets for pharmacological intervention. Although the first plant lipoxygenase (soybean LOX1) was discovered more than 60 years ago, the structural aspects of these enzymes were not studied until the mid 1990s. For the time being the crystal structures of various lipoxygenase-isoforms have been reported, and X-ray coordinates for numerous enzyme-ligand complexes are also available. This review focuses on recent developments in molecular enzymology of LOX and summarizes our current knowledge on the structural basis of LOX catalysis. Hypotheses explaining the reaction specificity of different isoforms as well as evolutionary aspects are reviewed and discussed. As the review is mainly intended to cover thematic priorities, which have not been reviewed in the past, a detailed discussion of the biological function of LOX goes beyond the scope of this review.